Patients with sciatica still experience pain and disability 5 years after surgery: A systematic review with meta‐analysis of cohort studies. (12th May 2016) - Machado, G.C.; Witzleb, A.J.; Fritsch, C.; Maher, C.G.; Ferreira, P.H.; Ferreira, M.L.
Abstract: Background and objective: The clinical course of patients with sciatica is believed to be favourable, but there is conflicting evidence on the postoperative course of this condition. We aimed to investigate the clinical course of sciatica following surgery. Databases and data treatment: An electronic search was conducted on MEDLINE, EMBASE and CINAHL from inception to April 2015. We screened for prospective cohort studies investigating pain or disability outcomes for patients with sciatica treated surgically. Fractional polynomial regression analysis was used to generate pooled means and 95% confidence intervals (CI) of pain and disability up to 5 years after surgery. Estimates of pain and disability (converted to a 0–100 scale) were plotted over time, from inception to last available follow‐up time. Results: Forty records (39 cohort studies) were included with a total of 13, 883 patients with sciatica. Before surgery, the pooled mean leg pain score was 75.2 (95% CI 68.1–82.4) which reduced to 15.3 (95% CI 8.5–22.1) at 3 months. Patients were never fully recovered in the long‐term and pain increased to 21.0 (95% CI 12.5–29.5) at 5 years. The pooled mean disability score before surgery was 55.1 (95% CI 52.3–58.0) and this decreased to 15.5 (95% CI 13.3–17.6) at 3 months, and further reduced to 13.1 (95% CI 10.6–15.5) at 5 years. Conclusions: Although surgery is followed by a rapid decrease in pain and disability by 3 months, patients still experience mild to moderate pain and disability 5 years after surgery. What does this review add?: This review provides a quantitative summary of the postoperative course of patients with sciatica. Patients with sciatica experienced a rapid reduction in pain and disability in the first 3 months, but still had mild to moderate symptoms 5 years after surgery. Although no significant differences were found, microdiscectomy showed larger improvements compared to other surgical techniques.